Influence of molybdenum on the hot-tensile properties of austenitic stainless steels - Tehovnik, Franc (Materiali in tehnologije, 2012)
Hot-tensile tests in the temperature range from 800 °C to 1200 °C were carried out on selected austenitic stainless steels containing mass fractions 0.6 % to 2.83 % of Mo with the aim being to study the effect of molybdenum on the mechanical properties. The tensile strength of the investigated steels decreased rapidly in the temperature range from 800 °C to 950 °C and slowly at the testing temperatures from 1000 °C to 1200 °C. In addition, the steel with the highest Mo content had a sharper decrease in the tensile strength. The temperature at which the maximum elongation was measured decreased with an increasing Mo content. It was found that molybdenum has a negative influence on the hot-ductility of austenitic stainless steels. In the steel with 2.83 % of Mo, the transformation from delta-ferrite to sigma-phase started at 1000 °C.
Keywords: austenitic stainless steels; avstenitno nerjavno jeklo; natezne lastnosti; tensile properties; molibden; molybdenum